2012
DOI: 10.5012/bkcs.2012.33.5.1686
|View full text |Cite
|
Sign up to set email alerts
|

Excess Volumes, Speeds of Sound, Isentropic Compressibilities and Viscosities of Binary Mixtures of N-Ethyl Aniline with Some Aromatic Ketones at 303.15 K

Abstract: Densities (ρ), Viscosities (η) and ultrasonic speeds (u) of pure acetophenone (AP), propiophenone (PP), p-methyl acetophenone (p-MeAP), p-chloroacetophenone (p-ClAP) and those of their binary mixtures with N-ethyl aniline (N-EA) as a common component, were measured at 303.15 K over the entire composition range. These experimental data were used to calculate the excess volume V E , deviation in ultrasonic speeds Δu, isentropic compressibility K s , intermolecular free length L f , acoustic impedance Z, deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…This fact is well known as the transport phenomenon and thermo-physical properties of mixed solvents. The present study is a continuation of our earlier research [1][2][3][4] on thermodynamic properties of binary liquid mixtures. The liquids were chosen in the present investigation on the basis of their industrial importance.…”
Section: Introductionmentioning
confidence: 69%
“…This fact is well known as the transport phenomenon and thermo-physical properties of mixed solvents. The present study is a continuation of our earlier research [1][2][3][4] on thermodynamic properties of binary liquid mixtures. The liquids were chosen in the present investigation on the basis of their industrial importance.…”
Section: Introductionmentioning
confidence: 69%
“…Previous investigations have been carried out on p-chloroacetophenone [3][4][5] and anilines [6][7][8][9] and amines [10,11] have been reported. Literature survey shown that no work has been executed on p-chloroacetophenone and aniline, N-methylaniline and N,N-dimethylaniline at 303.15 to 318.15 K. The effect of molecular size, chain length, shape and extent of molecular association of aromatic and aliphatic amines on volumetric, viscometric and acoustic properties of binary liquid mixtures containing hydrocarbons, esters and alcohols have been studied earlier [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We reported in our earlier communications [5, 6] excess volumes, sound velocities and viscosities for the binary mixtures of N -ethyl aniline and N , N -dimethyl aniline with aromatic ketones. A survey of literature has shown that thermodynamic properties of amines with 2-propanone, 2-butanone and 2-pentanone were reported [79].…”
Section: Introductionmentioning
confidence: 99%